Supramolecular Nanorods of (N-Methylpyridyl) Porphyrin With Captisol: Effective Photosensitizer for Anti-bacterial and Anti-tumor Activities - Khurana, Raman; Kakatkar, Aarti S.; Chatterjee, Suchandra; Barooah, Nilotpal; Kunwar, Amit; Bhasikuttan, Achikanath C.; Mohanty, Jyotirmayee (Frontiers in Chemistry, 2019)
Porphyrins, especially the 5,10,15,20-tetrakis(4-N-methylpyridyl) porphyrin (TMPyP), are well accepted as photosensitizers due to strong absorption from visible to near-infrared region, good singlet oxygen quantum yields as well as chemical versatility, all of which can be further modulated through planned supramolecular strategies. In this study, we report the construction of supramolecular nanorods of TMPyP dye/drug with captisol (sulfobutylether--cyclodextrin, (SBE7βCD)) macrocycle through host-guest interaction. The availability of four cationic N-methylpyridyl groups favors multiple binding interaction with the captisol host, building an extended supramolecular assembly of captisol and TMPyP. In addition to the spectroscopic characterizations for the assembly formation, the same has been pictured in SEM and FM images as nanorods of ~10 m in length or more. Complexation of TMPyP has brought out beneficial features over the uncomplexed TMPyP dye; enhanced singlet oxygen yield, improved photostability and better photosensitizing effect, all supportive of efficient photodynamic therapy activity. The Captisol:TMPyP complex displayed enhanced antibacterial activity towards E. coli under white light irradiation as compared to TMPyP alone. Cell viability studies performed in lung carcinoma A549 cells with light irradiation documented increased cytotoxicity of the complex towards the cancer cells whereas reduced dark toxicity is observed towards normal CHO cells. All these synergistic effects of supramolecular nanorods of Captisol-TMPyP complex make the system an effective photosensitizer and a superior antibacterial and antitumor agent.